Determinants of the Equity Price of Main Board Index Companies - Komariah, Siti; Gusni, Gusni; Riantani, Suskim (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The stock price has consistently varied over time in the capital market and can be influenced by a range of internal and external factors. This study aims to identify the elements that investors take into account when making investment decisions on the Main Board Index of the Indonesian stock market, as well as the factors that determine share prices. The study utilized data gathered between 2018 and 2022, from 106 companies listed on the main board index using a purposive sampling method. Panel data regression techniques have been utilized to elucidate the determinants of the firm equity price. Research findings denote that profitability as measured by earnings per share (EPS) and return on assets (ROA), along with the size and value of the firm, contribute positively to equity prices. Conversely, the capital structure exerts a negative impact on share prices, while dividend policy does not affect stock prices. Our findings underscore the significance for investors to consider on factors within a company beside external when processing information and deliberating on investment choices. Keywords: Equity Price; Determinant Factors; Main Board Index; Panel Data; Capital Market